Connecting to place through creative tourism - Bakas, Fiona Eva (2020)
Within creative tourism, place-based specificities are sources of inspiration as well as strategic elements to foster distinctive initiatives with local resonance. Place, holistically conceived, comprises the physical environment, cultures, intangible and tangible heritage, and the people inhabiting the locale. This chapter analyzes how creative tourism experiences developed within CREATOUR integrate elements that connect visitors to place, enabling participants to feel a sense of belonging in the place visited. The authors engaged in a collective reflexive exercise about the creative tourism experiences developed that revealed four dimensions or ways of connecting to place: through the site and materials, the activity, storytelling, and socializing. The specific site where the experience occurs can directly integrate macro and micro scales of place, from landscape to venues, while endogenous materials used within it encourage participants to directly interact with the landscape and its natural resources. Ensuring that the experience itself includes making items that are coherent with local culture, traditions, and crafts can also meaningfully connect participants to place. Integrating storytelling into the experiences, for example, by using theatrical tools or personal stories told by locals, connects visitors to the local place through its history, narratives, and local characters. Finally, moments for socializing within the creation activities as well as in social moments such as a picnic or walk play an important role in allowing visitors to slow-down, relax, and absorb the ‘feeling of place’. Integrating all four elements into a creative tourism experience helps immerse participants in place-specific culture and history in innovative manners, motivate visitors to participate, and create memorable experiences. This chapter may be useful to individuals developing creative tourism activities.